Hubungan antara Penggunaan Gadget terhadap Konsentrasi Belajar Siswa Pada Mata Pelajaran Matematika Kelas V UPTD SD Negeri 122345 Pematangsiantar - Sianipar Yulianty; Lastria Br. Sitompul; Radode Kristianto Simarmata (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The development of digital technology has brought major changes to the world of education, one of which is through the use of gadgets by elementary school students. Gadgets can provide benefits as a learning medium, but excessive and uncontrolled use has the potential to reduce students' learning concentration, especially in Mathematics subjects which require high focus and precision. This research aims to determine the relationship between gadget use and students' learning concentration in Mathematics class V at UPTD SD Negeri 122345 Pematangsiantar. This research uses a quantitative approach with correlational methods. The population in this study was all 32 class V students, with a sampling technique using saturated sampling. Data collection was carried out through questionnaires, observation and documentation. The data analysis technique uses descriptive analysis and Product Moment correlation. It is hoped that the results of the research will provide an overview of the relationship between gadget use and student learning concentration and will be a consideration for teachers and parents in directing the use of gadgets wisely and productively.